Dissipative fault detection for time‐delay nonlinear Markov jump systems with measurement outliers under stochastic communication protocol - Wu, Zhihui; Ma, Siteng; Feng, Lichao; Chen, Dongyan; Hu, Tiantian (International journal of adaptive control and signal processing, 2024)
This article investigates the dissipative fault detection (FD) problem for time‐delay nonlinear Markov jump systems with measurement outliers in the case of partially unknown transition probabilities. The stochastic communication protocol is utilized to save network bandwidth, where the scheduling model is described via a Markov chain. An outlier‐resistant FD filter is constructed with the help of adaptive saturation function technology. The sufficient conditions are derived to ensure that the FD system satisfies the stochastic stability and stochastic strict dissipativity. In addition, an FD filter without saturation constraint is also designed to compare with the outlier‐resistant FD filter, which verifies that the outlier‐resistant FD filter weakens the influence of measurement outliers effectively. Finally, two examples are provided to demonstrate the feasibility and effectiveness of the designed FD scheme.